Modelling and analysis of the mechanical and forming behaviours of 3D warp interlock carbon woven fabrics according to the structural design parameters. Issue 2 (1st February 2023) - Korkmaz, Mehmet; Labanieh, Ahmad Rashed; Boussu, François; Okur, Ayşe
Abstract: The 3D warp interlock carbon fabrics, which have different structural properties, were produced and their tensile, bending, shear and formability properties were tested in our previous study. However, further analyses and modelling studies are needed to have an overall understanding of the specific and complex behaviours of the 3D warp interlock carbon fabrics. The 3D warp interlock fabrics contain more number of product properties, which are number of layers, two or more number of yarns groups, the parameters of binding warp yarns and so on, in comparison with the traditional woven fabrics. This phenomenon makes difficulties for designers to choose optimal structure to obtain last product properties. The mechanical and formability behaviours of 3D warp interlock carbon fabrics were analysed in terms of the structural design parameters in the study. Thanks to the carried out analyses, the new relationships could be revealed as well as the currently known connections were proven among the fabric parameters. The formability behaviour of 3DWIF has never been statistically modelled in the previous studies. Therefore, the models were developed to predict the mechanical and formability behaviours of the 3D warp interlock carbon fabrics to bring new perspective for literature. Revealed relationships and developed models help designers to determine the best structural solution for purposed properties as well as clarify the complex behaviours of 3D warp interlock fabrics.